Impact of untreated sewage and thermal effluent discharges on the air-sea CO2 fluxes in a highly urbanized tropical coastal region. (February 2022) - Muthukumar, C.; Balasubramaniyan, S.; Garlapati, Deviram; Bharathi, M. Durga; Kumar, B. Charan; James, R.A.; Ramu, K.; Ramanamurthy, M.V.
Abstract: Various biotic and abiotic factors regulate carbon dioxide (CO2 ) absorption and emission in coastal waters. Factors controlling the regional air-sea CO2 fluxes were studied in Tuticorin Bay, a highly urbanized region along the southeast coast of India. Significant spatial heterogeneity in the distribution of inorganic carbon components in the bay was observed based on the exposure to different anthropogenic pressures. Thermal effluent discharges made the south zone of the bay a strong CO2 source by enhancing heterotrophy. Untreated sewage discharges in the middle zone mediated eutrophic conditions leading to strong autotrophy and restricting the zone as a weak source of CO2. Irrespective of the anthropogenic stressors, biological processes dominated the air-sea CO2 fluxes in the Tuticorin Bay. The results indicated that micro-level studies are needed in understanding the carbon cycle in environments with multiple anthropogenic stressors. Graphical abstract: Unlabelled Image Highlights: Processes driving the CO2 distribution and fluxes were studied in Tuticorin Bay. Multiple anthropogenic pressures force significant spatial heterogeneity. Untreated sewage leads to eutrophy, and thermal discharges enhance heterotrophy. Biological processes dominate the air-sea CO2 fluxes irrespective of the stressors.